Boring polychaetes associated with Pycnodonte (Phygraea) vesicularis (Lamarck) from upper Cretaceous of Patagonia: A case of commensalism? - Brezina, Soledad Silvana (2014)
The presence of the oyster Pycnodonte (Phygraea) vesicularis (Lamarck) is recorded in the Maastrichtian mudstones of the Jagüel Formation. This species was free-lying and inhabited muddy bottoms in a shallow marine shelf with a low sedimentation rate. Their shells supported a diverse community including fungi, algae, sponges, cirripedes, bryozoans, phoronids, polychaetes and mollusks. The most conspicuous components of this community are the boring polychaetes. The aim of this work is to assess possible paleoecological relationships between the oysters and polychaetes. Eighty-nine specimens of P. (Ph.) vesicularis were studied and presence/ absence data were recorded. Most of the boring openings are located on the ventral margins and are perpendicular to the growth lines. Preferential distribution of borings on the external surface of valves and on the ventral margins suggests a syn-vivo colonization. The high density of polychaete traces on the valves is an evidence of aggregative behavior of these worms. Although the borings weakened the valve and reduced shell strength, this does not seem to have been lethal for the oysters because there is no evidence of borings opening on the external surface reaching the internal surface of the valve. This suggests that a symbiotic relationship probably existed between P. (Ph.) vesicularis and polychaetes and that this relationship could be classified as commensalism.